2020
DOI: 10.12973/eu-jer.9.2.511
|View full text |Cite
|
Sign up to set email alerts
|

Types of Use of Technologies by Spanish Early Childhood Teachers

Abstract: Young pupils engage with technology daily, however, the use that preschool teachers make of technologies and their level of digital expertise are largely unknown. The objective of this study was to determine how these teachers make use of ICT (Information and Communication Technologies) and the frequency with which they use them, as well as to explore the sociodemographic and professional factors related to the different uses. 477 preschool teachers from Spain took part in a survey. The questionnaire, validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
3
12
0
1
Order By: Relevance
“…The reasons given by the teachers were, in general, in agreement with the suggestions of the Greek curriculum and of NAEYC & FRC (2012) recommendations; the use of technology is a tool to support, complement and extend classroom learning and children's engagement. There is an agreement with earlier studies which indicated as reasons for computer use the acquisition/development of language and mathematical skills, children's motivation (Nikolopoulou, 2014a), as well as the technology as supportive-complementary learning tool (Nikolopoulou, 2014a;Gray et al, 2017;Romero-Tena et al, 2020). There is also an agreement as to that technology use took place, mainly, during the hour of free activities/play (Ljung-Djärf, 2008;Nikolopoulou, 2014aNikolopoulou, , 2014bNikolopoulou & Gialamas, 2015).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The reasons given by the teachers were, in general, in agreement with the suggestions of the Greek curriculum and of NAEYC & FRC (2012) recommendations; the use of technology is a tool to support, complement and extend classroom learning and children's engagement. There is an agreement with earlier studies which indicated as reasons for computer use the acquisition/development of language and mathematical skills, children's motivation (Nikolopoulou, 2014a), as well as the technology as supportive-complementary learning tool (Nikolopoulou, 2014a;Gray et al, 2017;Romero-Tena et al, 2020). There is also an agreement as to that technology use took place, mainly, during the hour of free activities/play (Ljung-Djärf, 2008;Nikolopoulou, 2014aNikolopoulou, , 2014bNikolopoulou & Gialamas, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…A study in Greece (Nikolopoulou, 2014a) investigated computer use and integration in 17 kindergartens in Greece and indicated that the most frequently reported purposesreasons for computer use regarded the acquisition/development of language and fine motor skills, as an incentive for learning, as a supervisory tool, and for entertainment (e.g., playing games). Romero-Tena et al (2020) investigated how preschool teachers made use of ICT, in Spain. ICT was used to prepare classroom work (planning, classroom posters) and as a classroom support learning tool (routines, games, to record audios etc).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, students' ability as learning subjects in operating computers was included in the good category. The success of ICT-assisted learning or electronic-based learning, in fact, must be supported by infrastructure, materials, utilization systems, and policies that have been established as regulations, both by the government and schools [45,46]. Empirically, teachers have implemented technology-assisted learning, such as the use of presentation media and instructional videos, but in some cases, it is still necessary to develop the learning potentials or resources available in schools.…”
Section: B Discussionmentioning
confidence: 99%
“…Selain itu, tidak adanya hardware (laptop, notebooks, dan komputer), kurangnya materi dan isi pengajaran, dan tidak adanya ketertarikan, dan kurangnya dukungan membuat guru mengalami berbagai hambatan ketika menggunakan teknologi di kelas (Liu & Pange, 2015). Media digital biasanya digunakan guru untuk hal-hal yang bersifat administrative seperti menyusun rencana pelaksanaan pembelajaran, melakukan penilaian, berbagi materi dengan sesame guru, dan berkomunikasi dengan orangtua (Romero-Tena et al, 2020). Di sisi lain, media digital sebenarnya memiliki banyak kegunaan untuk guru seperti sebagai alat pembelajaran yang dipakai untuk rutinitas, permainan, merekam video, membuat anecdote, dan mencari berbagai teknik dan metode belajar terbaru agar suasana kelas lebih bervariasi.…”
Section: Pendahuluanunclassified